2022
DOI: 10.3390/bs13010037
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Erosion of Human Capital: The Impact of Emotional Blackmail and Emotional Intelligence on Nurses’ Job Satisfaction and Turnover Intention

Abstract: Emotion is a compelling factor in the retention and job satisfaction of professionals, and the impacts of emotional feelings and reactions have become an indispensable issue in the nursing workforce. Drawing on the cognitive theory of emotions, this study bridges the research gap to investigate the relationships among emotional blackmail, emotional intelligence, job satisfaction, and turnover intentions of nurses. A cross-sectional design was used to collect data from a sample of 374 full-time nurses in Northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…This pattern emphasizes the crucial influence of job satisfaction on employees' intents to leave their current jobs. The research conducted by Alam and Asim (2019) among nurses in Karachi, Lo et al (2023) among nurses in Taiwan, and Chen et al (2023) among the young workforce in China collectively emphasize the inverse association between job satisfaction and turnover intent. These studies highlight the importance of elements such as support from the organization, emotional well-being, and possibilities for career growth in determining employees' likelihood to stay in their current positions.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…This pattern emphasizes the crucial influence of job satisfaction on employees' intents to leave their current jobs. The research conducted by Alam and Asim (2019) among nurses in Karachi, Lo et al (2023) among nurses in Taiwan, and Chen et al (2023) among the young workforce in China collectively emphasize the inverse association between job satisfaction and turnover intent. These studies highlight the importance of elements such as support from the organization, emotional well-being, and possibilities for career growth in determining employees' likelihood to stay in their current positions.…”
Section: Turnover Intentionmentioning
confidence: 99%
“…To deal with the problems nurses encounter at work and increase job satisfaction, emotional skills and tactics might be essential. EI may also serve as a stressrelieving buffer for nurses, resulting in higher work satisfaction (45)(46)(47). Because of the growing expectations and difficulties that nurses encounter in today's healthcare system, work satisfaction is particularly important.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Al-kharabsheh et al ( 2023), Eliyana et al (2019), and Muzakki and Pratiwi (2019) revealed that in today's modern business world, a number of companies are concentrating their efforts on finding ways to improve employee performance and job satisfaction. According to the findings of several studies, high levels of job satisfaction and employee performance can positively impact the frequency of absenteeism and the likelihood of employee turnover (Lo et al, 2023). In addition, Ayuvisda and Made (2019) reported that performance has been associated with the results of a process that refers to and is measured over a certain period based on organizational structure, rank (or group), position, quality of supervision, financial stability, prospects for advancement, social contacts, and labor relations.…”
Section: Introductionmentioning
confidence: 99%